PENGARUH KEPUASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN (Study Kasus Pada Dinas Pemberdayaan Masyarakat Dan Desa Di Kabupaten Malang) - frengky frengky (MAGISTER MANAJEMEN UNISMA, 2020)
This study examines the effect of satisfaction and work discipline on employee performance, as well as to know the effect of firm commitment to satisfaction and work discipline. In this research involving 57 respondents, all of whom are employees of community empowerment and village empowerment office in malang regency. Data analysis used is path analysis, and confirmatory factor analysis to confirm indicator that explain construct or variable. Confirmatory factor analysis results show that all indicators of each variable are able to explain the variable of job satisfaction and work discipline, employee performance through company commitment. From the analysis path (path analysis) found that there is influence of job satisfaction on commitment, The influence of work discipline on commitment, The influence of job satisfaction on employee performance, The influence of work discipline on employee performance, The influence of commitment to employee performance. The total influence between work discipline variables on positive employee performance can be interpreted that the higher the discipline of work hence the performance of employees will increase. Keywords: job satisfaction, work discipline, employee performance and commitment